Aglomeration as a form of a spatial organization of production and settlement of russian regions - F. F. Sharipov; D. K. Maksimov (Путеводитель предпринимателя, 2020)
Agglomeration as one of the ways the spatial organization of the economy was reviewed in this article. Definition, essence and mechanism of organization of agglomeration was given. Examples of successful existence and perspectives of Russian and Chinese agglomeration was given and Republic of Tatarstan was reviewed particularly. Key factors of organization and structuring of industry was listed in conclusion.